In the kingdom of ice : the grand and terrible polar voyage of the USS Jeannette - Sides, Hampton; Morey, Arthur (New York, New York : Random House Audio, 2014)
Recounts the ill-fated nineteenth-century naval expedition to the North Pole under the leadership of George Washington De Long that resulted in the sinking of the USS Jeannette and the crew's epic struggle for survival in the harsh and unforgiving Arctic environment.
Title from container.
Read by Arthur Morey.
Keywords: Bennett, James Gordon, -- 1841-1918.; De Long, George W. -- 1844-1881.; Jeannette (Steamer) -- History; Shipwrecks -- Arctic Ocean -- History -- 19th century; Shipwreck survival -- Arctic Ocean -- History -- 19th century; Shipwreck survival -- Siberia -- History -- 19th century; Audiobooks